Fiscal incentives for business R&D: Compendium of evidence on the effectiveness of innovation policy intervention - Christian Köhler; Philippe Larédo; Christian Rammer (National Endowment for Science, Technology and the Arts (NESTA), 2012)
This project is part of a broader activity to prepare a compendium of evidence on the effectiveness of innovation policy intervention funded by NESTA (the National Endowment for Science, Technology and the Arts) and coordinated by the Manchester Institute of Innovation Research. ZEW contributes to this activity in the field of R&D tax incentives. Based on a literature review on empirical findings of the effectiveness of R&D tax credits and other types of tax incentives in favour of R&D, conclusions on a proper design of such policy instruments are drawn.In addition to tax incentives, the overall project also considers direct support for business R&D through grants and loans, financial support programmes such as venture capital programmes, human resource programmes, innovation intermediaries, technology transfer schemes, cluster and network activities, IPR related measures, regulation and standardisation, and public procurement.
Keywords: 330